Haploinsufficiency of endogenous parathyroid hormone‐related peptide impairs bone fracture healing. (27th October 2013) - Wang, Yin‐He; Qiu, Yong; Han, Xiao‐Dong; Xiong, Jin; Chen, Yi‐Xin; Shi, Hong‐Fei; Karaplis, Andrew
Summary: Previous studies have demonstrated that endogenous parathyroid hormone‐related peptide (PTHrP) plays a central role in the physiological regulation of bone formation. However, it is unclear whether endogenous PTHrP plays an important function in enhancing bone fracture healing. To determine whether endogenous PTHrP haploinsufficiency impaired bone fracture healing, closed mid‐diaphyseal femur fractures were created in 8‐week‐old wild‐type and Pthrp +/− mice. Callus tissue properties were analysed 1, 2 and 4 weeks after fracture by radiography, histology, histochemistry, immunohistochemistry and molecular biology. The size of the calluses was reduced 2 weeks after fracture, and the fracture repairs were poor 4 weeks after fractures, in Pthrp +/− compared with wild‐type mice. Cartilaginous callus areas were reduced 1 week after fracture, but were increased 2 weeks after fracture in Pthrp +/− mice. There was a reduction in the number of ostoblasts, alkaline phosphatase (ALP)‐positive areas, Type I collagen immunopositive areas, mRNA levels of ALP, Runt‐related transcription factor 2 ( Runx2 ) and Type I collagen, Runx2 and insulin‐like growth factor‐1 protein levels, the number of osteoclasts and the surface in callus tissues in Pthrp +/− compared with wild‐type mice. These results demonstrate that endogenous PTHrP haploinsufficiency impairs the fracture repair process by reducing cartilaginous and bony callus formation, with downregulation of osteoblastic gene and protein expression and a reduction in endochondral bone formation, osteoblastic bone formation and osteoclastic bone resorption. Together, the results indicate that endogenous PTHrP plays an important role in fracture healing.